Comunidades vegetales de las transiciones terrestre-acuáticas del páramo de Chingaza, Colombia. - Schmidt-Mumm, Udo (2012)
High Andean paramo ecosystems are an important water resource for many towns, and major cities in this region. The aquatic and wetland vegetation of different paramo lakes, pond, swamps and bogs was studied according to the classical phytosociological approach, which is based on homogenous stands, but excludes any border phenomena or transitional zone. The present research aimed at determining the aquatic and wetland vegetation along different moisture gradients. A total of 89 species in 30 transects were reported, of which Crassula venezuelensis, Carex bonplandii, Callitriche nubigena, Eleocharis macrostachya, Ranunculus flagelliformis, R. nubigenus, Eleocharis stenocarpa, Galium ascendens y Alopecurus aequalis were present in more than one third of the transects. Numerical classification and indicator species analysis resulted in the definition of the next 18 communities: 1) Calamagrostis effusa, 2) Sphagnum cuspidatum, 3) Cyperus rufus, 4) Eleocharis stenocarpa, 5) Carex acutata, 6) Poa annua, 7) Valeriana sp., 8) Ranunculus flagelliformis, 9) Carex bonplandii, 10) Festuca andicola, 11) Muhlenbergia fastigiata, 12) Elatine paramoana, 13) Isoëtes palmeri, 14) Crassula venezuelensis, 15) Lilaeopsis macloviana, 16) Callitriche nubigena, 17) Potamogeton paramoanus and 18) Potamogeton illinoensis. The ordination of communities reveals the presence of three different aquatic-terrestrial gradients which are related to the life form structure of species that characterized the various communities. We concluded that patchiness and heterogeneity of the vegetation is mainly the result of alterations caused by human activities (burning, cattle raise and material extraction for road and dam construction).